Human Resource Accounting: Methods & Practices in Bangladesh - Bhattacharjee, Sutapa; Shourov, Reefat Zaman; Khan, A.K.M. Jakaria (AIUB Journal of Business and Economics, 2017)
Human resource is considered to be the most crucial and important asset of an organization since it controls all other resources. Usually, human resource was being ignored by traditional accounting since there was no scientific method to measure the value of human asset in monetary terms. Efforts, since 1960s, has been put forth to develop a mechanism to resolve the issue. Along with developing different mechanism, researchers became interested in a new field of study-human resource accounting. Now, human resource accounting encompasses the entire process of identifying and measuring data about human resources and communicating this information to interested parties. Both cost based and value based models are being used for human resource accounting. This paper aims to study the methods and practices of Human Resources Accounting in Bangladesh. A survey of the HR executives at different levels in the organizations of Bangladesh has been conducted for this purpose. The study reveals that, in Bangladesh, human resource accounting is yet to be spread out. The top management of some companies are not likely to take HRA practices with great importance. But the perception of HRA practices among Bangladeshi Nationals has been found to be positive.